The Burden of Malnutrition in Childhood Cancer in Malawi – Risk Regardless of Age. (13th August 2022) - Huibers, Minke H. W.; Manda, Geoffrey; Silverstein, Allison; Wanda, Watipaso; Mtete, Idah; Makuti, Samuel; Westmoreland, Kate D.; Mehta, Parth; Ozuah, Nmazuo W.
Abstract: Malnutrion among children with childhood cancer in low and middle income countries (LMICs) is prevelant. While national nutrition programs focus on children under 5 years, childhood cancer can occur regardless of their age. Through a single-center retrospective cohort in Lilongwe, Malawi, we aim to characterize the burden of age-related malnutrition among children diagnosed with cancer in Lilongwe, Malawi, and evaluate them for any associations with mortality. Four hundred and sixty-three children (63.5% ≥5 years and 58.3% males) were identified.The majority of children (63.3%) were malnourished; 23.1% had moderate acute malnutrition (MAM) and 40.2% had severe acute malnutrition (SAM). Malnutrition was more common in children ≥5 years (70.0%) compared to children <5 years (51.8%); p < 0.0001. Age <5 years (HR 1.6; 95%CI 1.1-2.3, p = 0.016) and presence of sever acute malnutrition (HR 1.6, 95%CI 1.1-2.3, p = 0.012) were both associated with increased mortality risk. Acute malnutrition was highly prevalent among children with cancer above 5 years of age. This age group is not prioritized among malnutrition programs in LMICs, hence there is a direct need to include children with cancer regardless of age in national nutrition guidelines in LMICs to give them acces to adequate nutritional support.